Neuromyelitis optica spectrum disorders: a review with a focus on children and adolescents - Paolilo, Renata Barbosa; Paz, José Albino da; Apóstolos-Pereira, Samira Luisa; Rimkus, Carolina de Medeiros; Callegaro, Dagoberto; Sato, Douglas Kazutoshi (Arquivos de Neuro-Psiquiatria, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare and severe inflammatory disorder of the central nervous system (CNS). It is strongly associated with anti-aquaporin 4 antibodies (AQP4-IgG), and it mainly affects young women from non-white ethnicities. However, ∼ 5 to 10% of all cases have onset during childhood. Children and adolescents share the same clinical, radiologic, and laboratory presentation as adults. Thus, the same NMOSD diagnostic criteria are also applied to pediatric-onset patients, but data on NMOSD in this population is still scarce. In seronegative pediatric patients, there is a high frequency of the antibody against myelin oligodendrocyte glycoprotein (MOG-IgG) indicating another disease group, but the clinical distinction between these two diseases may be challenging. Three drugs (eculizumab, satralizumab, and inebilizumab) have been recently approved for the treatment of adult patients with AQP4-IgG-positive NMOSD. Only satralizumab has recruited adolescents in one of the two pivotal clinical trials. Additional clinical trials in pediatric NMOSD are urgently required to evaluate the safety and efficacy of these drugs in this population.
Keywords: Aquaporin 4; Multiple Sclerosis; Myelin-Oligodendrocyte Glycoprotein; Myelitis; Optic Neuritis; Neuromyelitis Optica